UPAYA MENINGKATKAN HASIL BELAJAR SISWA DENGAN METODE BUZZ GROUP PADA SUB KONSEP SISTEM PERKEMBANGBIAKAN PADA TUMBUHAN DAN HEWAN DI KELAS IX.B SMP NEGERI 24 TANJUNG JABUNG TIMUR T.A 2021/2022 - Mikel Satriawan (JURNAL PENDIDIKAN DAN KEGURUAN, 2024)
The teacher is decisive in choosing a teaching method that is appropriate and easy forstudents to understand. Based on observations at SMP Negeri 24 Tanjab Timur, it is known that the implementation of the science (biology) teaching and learning process has not reached the desired level of success. This can be seen from the average exam for the first semester of class IX.B students in the 2020/2021 school year. Based on the observations that the author made while teaching in Class IX.B SMP Negeri 24 Tanjung Jabung Timur, it can be seen that the learning outcomes in the breeding system in plants and animals are still very low. Only a few students achieve a KKM score of 70. This study is a Classroom Action Research that aims to determine whether learning using the Buzz Group method can improve science learning outcomes of grade IX.B students, especially on the subject of breeding systems in plants and animals. This research was carried out up to three cycles consisting of cycle I, cycle II and cycle III. The use of the Buzz Group discussion method in the Integrated Science (Biology) class IX.B SMP Negeri 24 Tanjung Jabung Timur can improve student learning outcomes. This can be seen from the increase in learning outcomes obtained by students in each cycle, namely: 63% in cycle I; 70.8% in cycle II and 80.4% in cycle III.